Menumbuhkan Minat Anak Remaja Dalam Berwirausaha Pada Sekolah Minggu Kelas Remaja GPDI Eben Haezer Kotaraja - Westim Ratang; Andarias Kuddy (UNIVERSITAS CENDERAWASIH, 2018)
The goals to be achieved from this community service activity are: To equip youth to have an understanding of the importance of entrepreneurs and be able to work independently with proper business planning and management. The training that was carried out stimulated teenagers to be creative and innovative by making bags with paper raw materials and producing products from the paper newspaper raw materials. By participating in this service activity teenagers will understand the importance of entrepreneurial spirit in relation to the very limited employment opportunities lately and their mindset will change rather than become a civil servant but become an entrepreneur. These teenagers are formed into people who are confident, independent, creative, innovative and not easily discouraged.